THE EFFECT OF EXERCISE ON MENTAL HEALTH AND SOME ELEMENTS OF PHYSICAL FITNESS AMONG FEMALE TRAINEES IN FITNESS CENTERS AGED 30-40 YEARS - Marwah Ali Hamzah (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Sports have become more diverse and specialized to meet different individual needs. Some sports aim to improve physical fitness, others focus on muscle strengthening, and still others improve flexibility and balance. Exercise is of great importance in improving general health and physical fitness, enhancing muscle strength, flexibility, and endurance, burning calories, aiding weight loss, and reducing the risk of cardiovascular diseases. It also improves bone density and reduces the risk of osteoporosis. Objectives. The purpose of this paper is to identify the impact of exercise on the mental health and certain fitness components of female trainees aged 30-40 years at fitness centers. Method. The experimental method, with a single-group design, was used, as it was suitable for the research problem and sample. The research sample consisted of 13 female trainees at the (Go Fit) gym in Karbala Governorate. After completing all field research procedures and statistically analyzing the data. Results. The results of the study showed a significance value (p<0.05), women in this age group received significant benefits from exercise in improving their mental health and physical fitness. Conclusion. Exercise played an important role in improving the physical and psychological performance of women. Exercise contributes to promoting public health and preventing chronic diseases. The most important recommendation is that the researcher provides support and encouragement to women who exercise to promote their continued participation.